Downregulation of ABC Transporters in Non-neoplastic Tissues Confers Better Prognosis for Pancreatic and Colorectal Cancer Patients - Dvorak, Pavel; Hlavac, Viktor; Mohelnikova-Duchonova, Beatrice; Liska, Vaclav; Pesta, Martin; Soucek, Pavel (Journal of Cancer, 2017)
Transport of a wide variety of substrates, including xenobiotics, is one of the main functions attributed to human ATP-binding cassette (ABC) proteins. Overexpression of ABC genes is considered to be an important mechanism facilitating the development of chemoresistance. Relationships between the expression levels of ABC genes in tumor tissues and established clinicopathological features were extensively studied previously. The current study tested our hypothesis that the expression levels of ABC genes in non-neoplastic (control) tissues also provide important information in relation to the relevant tumor progression. Expression levels of all human ABC genes (48 protein coding and one pseudogene), measured by qRT-PCR, were bioinformatically analyzed. The data originated from four independently collected cohorts covering three types of tumors - breast, colorectal and pancreatic carcinomas. ABC gene expression profiles (signatures) in non-neoplastic tissues (matched to tumor samples from three different tumor types) were characteristically clustered into three main types - those with the vast majority of the genes downregulated, upregulated or heterogeneously regulated. The clusters with mostly downregulated and upregulated genes were shown to possess significant relations to good and poor prognostic markers, respectively, in pancreatic and colorectal cancers. The present findings support the theory that the expression of ABC genes in non-neoplastic tissues can significantly contribute to tumor pathogenesis. Suggested multi-gene panels, consisting of the reduced number of ABC genes, have the potential to be implemented as new prognostic markers, which are especially urgent in pancreatic cancer. The results can also stimulate further primary research in carcinogenesis.
Keywords: cancer; ABC transporters; ATP-binding cassette; profiles; gene expression